MICROBIOTA AND DEVELOPMENT OF GASTRO-INTESTINAL FUNCTION AND INFLAMMATION. (July 2016) - Indrio, F.
Abstract : During the third trimester of pregnancy and in the first days after birth, important processes of intestinal maturation take place. Although anatomical differentiation of the human gut is usually achieved within 20 weeks of gestation, the functional maturation of the gastrointestinal tract is occurs later and requires organized peristalsis and coordinated sucking and swallowing reflexes that are not established until 29–30 weeks and 32–34 weeks of gestations, respectively Sensory-motor gastrointestinal functions are strictly related to the infant's immune system which plays a crucial role in modulating appropriate and non-exaggerated responses to luminal antigens. This fundamental enteric function, known as "oral tolerance, " is based on the interaction between the luminal content (microbiota, food antigens and other molecules), the intestinal epithelium and the tolerogenic dendritic cells (DCs) from mesenteric lymph nodes of the gut associated lymphoid tissue (GALT), and is associated with specific cytokine patterns. It has been suggested that the early composition of the intestinal microbiota at birth can influence the correct ontogenesis of the gut barrier and motor and immune function through a complex neuroendocrine cross-talk. Consequences of prematurity like antibiotic usage, feeding type and being located in neonatal intensive care unit (NICU) may cause an intestinal dysbiosis that affects the intestinal integrity and disrupts the delicate balance between intestinal microbiota and the immune system of premature infants. An aberrant microbial colonization pattern might contribute to the development of an early traumatic inflammatory insult on the gut-brain axis with short and long term consequences on gastrointestinal well-being.